Brief advice and active referral for smoking cessation services among community smokers: a study protocol for randomized controlled trial. (December 2016) - Suen, Yi; Wang, Man; Li, William; Kwong, Antonio; Lai, Vienna; Chan, Sophia; Lam, Tai
Abstract Background Most smokers do not use smoking cessation (SC) services although it increases successful quits. Passive referral providing SC information to smokers is commonly used in SC studies. Little was known about active referral in the community setting. This study aims to motivate community smokers to quit by brief SC advice using a validated AWARD model (Ask, Warn, Advise, Refer and Do-it-again) that adjunct with active referral of smokers to various SC services in Hong Kong. Methods/Design This is a single-blinded, parallel three-armed cluster randomized controlled trial (RCT) with two treatment groups of (1) brief SC advice using the AWARD model, active referral to SC services plus a referral card and a health warning leaflet (active referral group) and (2) brief SC advice using AWARD model and health warning leaflet (brief advice group) and a control group receives general very brief advice with a self-help booklet. A total of 1291 smokers will be recruited from 66 clusters (recruitment sessions) with 22 will be allocated to each of the two intervention and one control groups. SC ambassadors will be trained for delivering the interventions and conducting telephone follow-up. The primary outcomes are self-reported 7-days point prevalence (PP) abstinence at 3 and 6 months follow-up. Intention-to-treat principle and multi-level regressions will be used for data analysis. Discussion This is the first RCT on assessing a model combining brief advice and active referral to SC services among community smokers. The results will inform the practices of SC services and intervention studies. Trial registration NCT02539875 (ClinicalTrials.gov registry; registered retrospectively on 22 July 2015)